Numerical Study on the Effect of Tunnel Slope on Smoke Exhaust Performance in Metro Tunnels - Yuxuan Yang; Qianbo Zhang (Fire)
Utilizing the intermediate air shaft for smoke exhaust is one of the crucial emergency ventilation methods in metro tunnel fires. To study the impact of metro tunnel slope on smoke exhaust performance of intermediate air shaft, this paper employs numerical simulation to conduct research from the following aspects: the longitudinal distribution of ceiling smoke temperature, visibility distribution, smoke layer height, and the smoke exhaust efficiency of intermediate air shaft. The results demonstrate that as the tunnel slope increases, the maximum ceiling temperature decreases, and the visibility at dangerous height increases. The smoke layer height on the downhill side of a sloped tunnel is higher than that of a horizontal tunnel, while the smoke layer height on the uphill side is lower. Under single-side smoke exhaust mode, the smoke exhaust efficiency of the 2# intermediate air shaft rises as the tunnel slope increases. However, under air supply plus smoke exhaust mode, the smoke exhaust efficiency of the 2# intermediate air shaft decreases with the growing tunnel slope.